Postoperative Imaging after Impingement Surgery - Dietrich, Tobias Johannes; Grob, Karl; Kim, Chan-Hi Olaf (Seminars in Musculoskeletal Radiology, 2017)
In addition to the patient's medical history and clinical evaluation, conventional radiographs and magnetic resonance imaging (MRI) are important tools to indicate appropriate conservative treatment or even revision surgery in patients with symptoms after surgical management of femoroacetabular impingement (FAI). We present an overview of current evidence in postoperative imaging after impingement surgery. Undercorrection of the underlying osseous FAI configuration is the most frequent indication for revision surgery within the first 2 years after index FAI surgery. Femoral neck fractures, iatrogenic chondral injuries, early conversion to total hip arthroplasty, loose bodies, and heterotopic ossifications are rare but typical early complications after surgical treatment of FAI. Abnormal MRI findings after FAI surgery such as intra-articular adhesions, labral tears, cartilage defects, and anterior capsular defects are common findings in both asymptomatic and symptomatic postoperative patients. Avascular necrosis of the femoral head is an extremely rare complication after surgical treatment of FAI.
Keywords: femoroacetabular impingement; arthroscopy; surgical dislocation of the hip; postoperative; MRI